2022
DOI: 10.32604/cmc.2022.021102
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Based Intelligent Handwritten Document Recognition

Abstract: This paper presents a handwritten document recognition system based on the convolutional neural network technique. In today's world, handwritten document recognition is rapidly attaining the attention of researchers due to its promising behavior as assisting technology for visually impaired users. This technology is also helpful for the automatic data entry system. In the proposed system prepared a dataset of English language handwritten character images. The proposed system has been trained for the large set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Among other things, the leadership factor has been brought to the fore by the financial crisis of 2008 [41] [42], with many calling the crisis a leadership crisis, particularly the leadership of the big banks in the premier United States of America going astray [43][44] [17][45] [46]. Thus, leadership appears to become an increasing factor of importance [47] [48], and the performance of companies and their public standing is explained in terms of their leadership, represented by CEOs, Presidents/Chairman and Boards, and the workforce [49] [50]. They are all comrades in -in-armsfor public service and the people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among other things, the leadership factor has been brought to the fore by the financial crisis of 2008 [41] [42], with many calling the crisis a leadership crisis, particularly the leadership of the big banks in the premier United States of America going astray [43][44] [17][45] [46]. Thus, leadership appears to become an increasing factor of importance [47] [48], and the performance of companies and their public standing is explained in terms of their leadership, represented by CEOs, Presidents/Chairman and Boards, and the workforce [49] [50]. They are all comrades in -in-armsfor public service and the people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of this, a machine is trained to correctly identify Pashto handwritten characters that have never been seen before. With the help of this dataset ( 7 ), we trained and tested three FFNN models (Model 1 with a 1-ReLU layer, Model 2 with 2-ReLU layers, and Model 3 with 3-ReLU layers) using the backpropagation algorithm. Sample images of user-defined handwritten text were used to test the proposed overall system performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been demonstrated that a patient's handwriting can be used to identify them. Hyper-parameters and model parameters can differ significantly, as demonstrated by (7). Some hyper-parameters, such as the number of epochs, hidden units, hidden layers, Learning Rate (LR), kernel size, and activation function, must be set before training begins.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the innumerable benefits that this technological advancement has provided to societies around the world, there are significant drawbacks to the vast amount of readily available information at the hands of average people. This has been made even more apparent with the rampant spread of misinformation during the height of the COVID-19 pandemic [1,2,3,4,5]. The overarching issue is that the internet has produced an environment where people can take their healthcare into their own hands, as opposed to relying on licensed medical professionals for diagnosis, advice, and treatment.…”
Section: Introductionmentioning
confidence: 99%